The China syndrome: Local labor market effects of import competition in the United States - David H. Autor; David Dorn; Gordon H. Hanson (Institute for the Study of Labor (IZA), 2013)
We analyze the effect of rising Chinese import competition between 1990 and 2007 on U.S. local labor markets, exploiting cross-market variation in import exposure stemming from initial differences in industry specialization and instrumenting for U.S. imports using changes in Chinese imports by other high-income countries. Rising imports cause higher unemployment, lower labor force participation, and reduced wages in local labor markets that house import-competing manufacturing industries. In our main specification, import competition explains one-quarter of the contemporaneous aggregate decline in U.S. manufacturing employment. Transfer benefits payments for unemployment, disability, retirement, and healthcare also rise sharply in more trade-exposed labor markets.
Keywords: F16; H53; J23; J31; 330; trade flows; import competition; local labor markets; China